2017
DOI: 10.15171/joddd.2017.026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro properties of periodontal ligament stem cells derived from permanent and deciduous teeth

Abstract: Background. Stem cells have contributed to the development of tissue-engineered-based regenerative periodontal therapies. In order to find the best stem cell sources for such therapies, the biologic properties of stem cells isolated from periodontal ligaments (PDL) of deciduous (DePDLSC) and permanent (PePDLSC) teeth were comparatively evaluated. Methods. PDL stem cells were isolated from six sound fully erupted premolars and six deciduous canines of healthy subjects. In vitro biologic characteristics such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…In our study, we could also isolate MSCs from the dental pulp of both primary and permanent teeth, which is in accordance with Naz et al 14 We could also isolate MSCs from PDL, which is in accordance with Khoshhal et al 17 We first isolated a cell population by its plastic-adherent property, as described by Friedenstein et al 18 Our results indicate that gingival connective tissue-derived MSCs are CD90+, CD105+, and CD45−, which is in accordance with Mitrano et al, who had similar results. 15 We were able to induce osteogenic, chondrogenic, and adipogenic differentiation of stem cells under specific differentiation media, which is in agreement with Pittenger et al 19 and Nöth et al, 20 who described the multilineage potential of adult BM-MSCs.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we could also isolate MSCs from the dental pulp of both primary and permanent teeth, which is in accordance with Naz et al 14 We could also isolate MSCs from PDL, which is in accordance with Khoshhal et al 17 We first isolated a cell population by its plastic-adherent property, as described by Friedenstein et al 18 Our results indicate that gingival connective tissue-derived MSCs are CD90+, CD105+, and CD45−, which is in accordance with Mitrano et al, who had similar results. 15 We were able to induce osteogenic, chondrogenic, and adipogenic differentiation of stem cells under specific differentiation media, which is in agreement with Pittenger et al 19 and Nöth et al, 20 who described the multilineage potential of adult BM-MSCs.…”
Section: Discussionsupporting
confidence: 89%
“…A question raised based by this evidence, is, whether PDLSCs from deciduous teeth possess a greater osteogenic potential than those from permanent teeth. Khoshhal and colleagues, carried out a study comparing the osteogenic properties of PDLSCs from deciduous teeth versus PDLSCs from permanent teeth [39]. Teeth were sourced from different subjects, with osteogenic potential was assessed by AR staining and ALP activity.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in 2004, Seo et al isolated and identified PDLSCs from human impacted wisdom teeth for the first time [56]. In addition to wisdom teeth, PDLSCs can be extracted from permanent tooth root surfaces [63], deciduous tooth [64][65][66], or even inflammatory periodontal tissues [67]. However, PDLSCs derived from different environments display different properties related to proliferation and osteogenic potential.…”
Section: Periodontiummentioning
confidence: 99%